1997
DOI: 10.1111/j.1460-6984.1997.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating intervention for language impaired children: a review of the literature

Abstract: Intervention studies are divided into those which have examined the effectiveness of specific techniques and those that have attempted to examine eficacy within the clinical context. Of the specific techniques, imitation and recasting or expansion have been the most commonly examined. Results suggest that they may be equally usejid in reaching targets but that input in context has more chance of generalising. Combinations of techniques such as 'milieu teaching' seem especially promising. Evaluation of general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Law [4] reported that treatment evaluation refers to several levels of accountability: effectiveness, efficiency, effects and efficacy. 'Effectiveness' refers to whether a treatment can be shown to work or not insofar as it alters the course of a disorder.…”
Section: Types Of Efficacy Studiesmentioning
confidence: 99%
“…Law [4] reported that treatment evaluation refers to several levels of accountability: effectiveness, efficiency, effects and efficacy. 'Effectiveness' refers to whether a treatment can be shown to work or not insofar as it alters the course of a disorder.…”
Section: Types Of Efficacy Studiesmentioning
confidence: 99%
“…A cursory examination of the natural communication literature indicates that much attention has been paid to comparing and contrasting different approaches to communication interventions (eg, Creaghead, 1999;Goldstein, Kaczmarek, & Hepting, 1994;Hepting & Goldstein, 1996;Law, 1997;Santos & Lignugaris/Kraft, 1997). Research on the effectiveness of natural learning environment interventions continues to grow and expand (Barnett, Carey, & Hall, 1993;Dunst, Bruder, et al, 2001;McWilliam, 1992;Odom, Favazza, Brown, & Horn, 2000;Prizant & Wetherby, 1998;Santos & Lignugaris/Kraft, 1997).…”
mentioning
confidence: 95%
“…Despite the strategic promotion of ‘evidence‐based practice’ (EBP) within the UK since the early 1990s, speech and language therapists do not routinely carry out research into the effectiveness of the services they provide. One of the many complex, contributory factors may be the methodological challenges involved in conducting a robust intervention study which are frequently reported in the literature (Eayers and Jones 1992, Law 1997, Roulstone et al 1999, Bishop and Leonard 2000, Glogowska 2001, Pring 2004, 2005). Cultural reasons may also play a part.…”
Section: Introductionmentioning
confidence: 99%